A Guide to Reading Aquinas’ Academic Sermons - Klooster, Anton ten (Biblica et Patristica Thoruniensia, 2017)
Przewodnik po lekturze kazań akademickich Akwinaty Recenzja książki: Randall B. Smith, Reading the Sermons of Thomas Aquinas: A Beginner’s Guide, Steubenville, Emmaus Academic, 2016, xxxiv + 342 pp., ISBN: 978-1-941447-97-0